Inhibitory Powerof Lactic Acid Bacteria (BAL) from Cincaluk against pathogenic bacteria (Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus)and protease enzyme production - Povy Hutabarat; Nursyirwani Nursyirwani; Irwan Effendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Lactic acid bacteria (BAL) have the ability to inhibit the growth of pathogenic bacteria. BAL is bacterium that has an important role in the processof fermentation of organic materials. BAL can be found in traditional fishery products such as cincaluk (fermented shrimp). This study was conducted from February to April 2018. Test of isolate activity of BAL and protease enzyme was carried out at Marine Microbiology Laboratory, Faculty of Fisheries and Marine Scince, University of Riau.The study aimed was to examine the BAL activity of cincaluk against pathogenic bacteria and tested the protease enzyme produced by BAL from the cincaluk produced the community in Bengkalis and Tembilahan, Riau. This research used survey method where fresh cincaluk sample was used as abservation object in isolating the BAL and testing antagonism against three different pathogenic bacteria (Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus). The results of antagonism test showed that all bacterial isolated have ability to inhibit the growth of the three pathogenic bacteria. The highest inhibition zone P.aeruginosawas demonstrated by a GT isolate (11.0 mm), toward the highest inhibition zone against E. coliwas indicated by PB isolate (8.7 mm), and toward S. aureuswasdemonstrated by MB isolate (6.6 mm). All bacterial isolates produced protease enzyme indicated by clear zone around the colonies on skim milk medium. Keywords: BAL, Antagonism, Inhibition zone, Pathogens, Protease